QUANTITATIVE ANALYSIS OF FINANCIAL INDICATORS IN A ROMANIAN PUBLIC INSTITUTION: THE ROLE OF INTERNAL AUDIT IN PUBLIC FINANCIAL MANAGEMENT - UDRESCU LUCIA-MARIA (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie)
This paper aims to analyze the financial performance of Romania's National Public Pension House (CNPP) and evaluate the role of internal audit in public financial management. Public institutions, such as the CNPP, manage substantial financial resources derived from taxes, fees, and non-refundable sources like the National Recovery and Resilience Plan (PNRR). These funds are essential for providing public services, including pensions and social security benefits. Effective management and oversight of these resources are crucial for ensuring transparency, efficiency, and accountability. The study employs a quantitative analysis of financial indicators over the past five years, focusing on trends and the impact of internal managerial control deficiencies on the institution's financial performance. By using linear regression models, the research examines key performance metrics such as Working Capital, Working Capital Requirement, and Net Treasury. The findings reveal fluctuating trends influenced by the pandemic and other socioeconomic factors, highlighting the importance of robust internal controls and audits. Additionally, the study underscores the significance of internal audit functions in enhancing governance, identifying risks, and ensuring compliance with regulations. These mechanisms are critical for maintaining financial stability, optimizing resource management, and supporting strategic decision-making. The insights gained from this analysis provide valuable recommendations for policymakers and public administration officials to strengthen internal audit practices and improve financial management within public entities. The research concludes that regular audits and rigorous internal controls are essential for sustaining the financial health and operational efficiency of institutions like the CNPP, ultimately ensuring the reliability of pension payments and other financial obligations